HJT low-temperature conductive silver paste for nickel plate printing and preparation method of HJT low-temperature conductive silver paste
By using raw materials such as micron-grade silver powder and sub-micron-grade silver powder in HJT low-temperature conductive silver paste, combined with sulfonyl dianiline and resin, the conductive and flux resistance performance problems of the paste in nickel plate printing are solved, and efficient Silver paste preparation, suitable for the promotion of HJT solar cells.
Patent Information
- Application Number
- CN202411276911.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-31
AI Technical Summary
The existing HJT low-temperature conductive paste has problems such as poor ink return, dummy printing, and uneven thickness of printing grid lines during nickel printing, and it is difficult to meet the requirements of conductivity, flux resistance and printing properties at the same time, which affects the solar cell. Photoelectric conversion efficiency and industrial application.
The HJT low-temperature conductive silver paste composed of micron-scale silver ball powder, sub-micron-scale silver powder, organic solvent, curing agent and resin is prepared by mechanical mixing and centrifugal dispersion process, and sulfonyl dianiline is added to improve flux resistance performance, and Grinding is performed by a three-roll mill to improve viscosity and rheological properties to form a slurry suitable for nickel plate printing.
It realizes silver paste with excellent flux resistance, strong adhesion, good conductivity and high photoelectric conversion efficiency under low temperature conditions. It is suitable for nickel plate printing, reduces the light-shielding part of the battery and improves solar energy utilization efficiency. , and suitable for the promotion of new printing technologies.
Smart Images

Figure CN119230160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer-based electronic paste materials, and in particular to a HJT low-temperature conductive silver paste for nickel plate printing and a preparation method thereof. Background Art
[0002] According to the type of silicon wafer in crystalline silicon cells, photovoltaic cells can be divided into P-type cells and N-type cells. P-type cells mainly include BSF cells and PERC cells, and BSF cells were replaced by PERC cells around 2016. At present, the photoelectric conversion efficiency of PERC cells produced by various battery manufacturers is close to the theoretical extreme value. Due to technological updates and large fluctuations in silver prices in the market, the industry has abandoned PERC cells and turned to research on N-type cells with higher extreme efficiency.
[0003] N-type cells refer to solar cells that form a P+ / N-type structure by doping P elements into N-type semiconductor materials. They have the characteristics of high conversion efficiency, high bifaciality, low temperature coefficient, no light decay, good weak light effect, and longer carrier life. N-type cells mainly include TOPCon, HJT and IBC, with theoretical maximum efficiencies of 28.7%, 29.2% and 29.1% respectively, all higher than PERC's 24.5%.
[0004] The HJT cell in the N-type cell uses cheap amorphous silicon as the emission layer. The entire process is completed at 200°C, which consumes less energy and avoids the damage to the silicon wafer caused by thermal stress generated by traditional cell processes at high temperatures. In addition, it also has the characteristics of perfect passivation effect, high stability, and high electron mobility. It is worth noting that HJT is expected to form a stacked cell with perovskite and become the mainstream cell process of the next generation.
[0005] Due to the characteristics of HJT low-temperature process, the production experience of traditional PERC slurry cannot be applied to the research and development of low-temperature slurry. The high technical barriers make it difficult for existing low-temperature conductive slurries to meet various needs at the same time. Therefore, international markets such as Japan's Kyoto Electronics, the United States DuPont, and domestic paste companies such as Dico, Polymer and Jingyin are all launching differentiated products.
[0006] Solar cells are actually made up of multiple cells connected in series through welding ribbons, and flux needs to be applied during the welding process. The flux is usually an organic acid, which will corrode the interface between the silicon wafer and the secondary grid electrode, erode the grid line structure, and have an adverse effect on the photoelectric conversion efficiency of the battery, resulting in battery performance degradation. In current actual production, in order to balance the electrical properties, mechanical properties and printability of the conductive paste, the industry has a high tolerance for the flux resistance of the paste, and there are almost no researchers who specifically study improvements in this area. However, if the adverse effects of the flux on the cell are ignored, the researchers need to invest more energy in improving the photoelectric conversion efficiency of the cell, which is obviously more difficult. In addition, in the process of realizing industrial applications, the printability, stability, and friction resistance of the paste are also extremely important parameters. Therefore, when the paste meets the basic requirements of the manufacturer, it is more strategic to develop a paste with high resistance to flux corrosion.
[0007] In addition, with the low cost and high efficiency of the industry, the battery metallization method has also changed greatly. The industry is improving from the screen printing mode with mesh knots to the steel plate or nickel plate printing mode without mesh knots, and from the screen printing 23um opening to the narrower 12um opening. Due to the changes in the parameters of the screen material and the printing process, conventional HJT pastes generally have problems such as poor ink return, virtual printing, uneven thickness of the number of printed grid lines, and even inability to print during the printing process. Among them, too high or too low silver powder content will have an adverse effect on the paste. Too low will lead to low paste viscosity, poor aspect ratio after printing, and serious resin overflow; too high will not be easy to disperse in the solvent, and it is easy to form large particles during the grinding process, which will weaken the electrical performance.
[0008] There is an optimal ratio range between the slurry and the organic system. Choosing inappropriate resins and solvents may result in poor tissue density after the slurry is cured. In addition to being intolerant to flux, adhesion and electrical properties will also be affected. Therefore, developing slurries that are suitable for nickel plates or steel plates will be more conducive to the development of the country's photovoltaic industry. Summary of the invention
[0009] In view of the above problems existing in the prior art, the present invention provides a HJT low-temperature conductive silver paste for nickel plate printing and a preparation method thereof. The conductive silver paste prepared by the present invention has good conductivity, good printability when printed on a non-mesh nickel plate, strong adhesion, and excellent resistance to flux, which solves the efficiency loss caused by the series connection of multiple battery cells by welding with welding strips, and effectively promotes the promotion of heterojunction solar cells.
[0010] The technical solution of the present invention is as follows:
[0011] A HJT low-temperature conductive silver paste for nickel plate printing, the conductive silver paste is composed of the following raw materials in percentage by mass:
[0012] Micron-grade silver ball powder and silver flake powder 50-75%, submicron-grade spherical silver powder 18-44%, organic solvent 2-4%, curing agent 0.5%-1.5%, resin 2-4%, and auxiliary agent 0-1%.
[0013] Preferably, in the micron-sized silver ball powder and silver flake powder, the mass ratio of silver ball powder to silver flake powder is 2-3:6-7, the median particle size of the silver ball powder is 1-2um, and the median particle size of the silver flake powder is 2-4um; the median particle size of the submicron-sized spherical silver powder is 100-900nm.
[0014] Preferably, the organic solvent comprises one or more of the following raw materials: pinene alcohol, oleic acid, butyl carbitol, butyl carbitol acetate, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dihydroacetic acid pine oil, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
[0015] Preferably, the curing agent includes one or more of the following raw materials: polyetheramine, polyamide, dicyandiamide, sulfonyl dianiline, meta-xylylenediamine, hexahydrophthalic anhydride, methylhexahydrophthalic acid dry, tetrahydrophthalic acid dry, 2-ethyl-4-methylimidazole, modified amine, modified imidazole, blocked polyamine, blocked isocyanate.
[0016] More preferably, the curing agent contains sulfonyl dianilide.
[0017] Preferably, the resin is selected from one or more of glycidyl ether epoxy resins, glycidyl ester epoxy resins, glycidyl amine epoxy resins, aliphatic epoxy compounds, alicyclic epoxy compounds, and modified epoxy resins.
[0018] Preferably, the auxiliary agent includes one or more of silane coupling agent, silicone oil, fluorosilicone, hydrogenated castor oil, polyvinyl pyrrolidone, lactic acid monoglyceride, sodium dodecyl sulfate, fumed silica, polyamide wax, BYK11, BYK10 and BYK354.
[0019] Furthermore, the various types of silver powders are all mature commercial products produced on the market.
[0020] Furthermore, the effect of the organic solvent is to disperse the micron and submicron silver powder, curing agent and additives, and to make the slurry form a fluid with good appearance and metallic color during the mechanical mixing process. The composition of various organic solvents can effectively regulate the viscosity and rheological properties of the slurry.
[0021] Furthermore, the curing agent functions to cure the resin to form a cross-linked structure.
[0022] Furthermore, the resin acts as a binder in low-temperature silver paste, which can provide the paste with properties such as friction resistance and high conductivity. Among them, the glycidyl ether epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol epoxy resin, biphenyl epoxy resin, etc.
[0023] Furthermore, in addition to the above optional raw materials, the resin can also be mixed with acrylic resin and melamine urea-formaldehyde resin.
[0024] Furthermore, there are many types of additives, which can change the properties of the slurry.
[0025] The present invention also provides a method for preparing the conductive silver paste, comprising the following steps:
[0026] (1) mixing a resin, an additive, and an organic solvent of a required mass, and obtaining a uniform and transparent organic system by centrifugal dispersion to obtain a first organic carrier;
[0027] (2) adding a curing agent to the first organic carrier obtained in step (1), and mixing uniformly by mechanical stirring or by using a high-speed centrifuge to obtain a second organic carrier;
[0028] (3) adding the micron-sized silver ball powder, silver flake powder, and submicron-sized spherical silver powder to the second organic carrier in three portions, stirring evenly after each addition, until all the powder is added and stirred into a slurry, and placing the slurry in a centrifuge for centrifugal dispersion and degassing;
[0029] (4) The slurry obtained in step (3) is ground and dispersed by a three-roll mill, and then collected. The collected slurry is centrifuged again, and a finished product with a metallic color is obtained after degassing.
[0030] Preferably, in steps (1) and (2), the centrifuge speed is 1200-1800 rpm, and the centrifugation time is 1-5 min, respectively;
[0031] Preferably, in steps (3) and (4), the speed of the centrifuge is 500-600 rpm, and the centrifugation time is 1-2 min, respectively.
[0032] Preferably, in step (4), the initial roll spacing and the final roll spacing of the three-roll mill are set to 90-30um, 60-20um, and 45-15um, and the rolling speed is less than 200rpm.
[0033] Furthermore, in steps (1) and (2), the partially insoluble resin or curing agent can be mixed with other diluents in proportion. If it is difficult to dissolve, it can be preheated, but the temperature does not exceed 70°C.
[0034] Furthermore, during the centrifugal operation of steps (3) and (4), the rotation speed is reduced in order to avoid excessively high centrifugal speed and excessively long centrifugal time causing the slurry to heat up and trigger the resin reaction after the addition of silver powder.
[0035] The beneficial technical effects of the present invention are:
[0036] The present invention provides a low-temperature heterojunction (HJT) battery conductive silver paste suitable for nickel plate printing and having excellent flux resistance and a preparation process thereof, wherein the paste has the following excellent technical advances.
[0037] 1. Strong resistance to flux:
[0038] The conductive silver paste provided by the present invention has good flux resistance, and effectively reduces the influence of flux on the grid line during the process of integrating multiple battery cells in series with solder strips. This is because the lattice of indium tin oxide (ITO) on the outer surface of the battery is a central cube, six oxygen atoms occupy the vertices, and two oxygen atom vacancies are left, and there is a sulfonyl group in sulfonyl dianilide, and the electron cloud of its oxygen atom overlaps with ITO, causing the ITO lattice to be distorted, and some oxygen atoms fill in the lattice vacancies, and the tight bonding makes the cured grid line have a certain resistance to the erosion of acidic flux, thereby improving the overall flux resistance of the paste.
[0039] 2. Suitable for nickel plate printing, with good linearity, strong adhesion, smooth linear shape and strong friction resistance after printing:
[0040] (1) The silver powder size selected by the present invention is relatively reasonable. The large volume and high-quality silver powder curbs the precipitation and diffusion of the solvent. While not affecting the electrical performance, it ensures that the slurry is printed using a nickel plate. The grid lines after printing are relatively flat and maintain a narrow and high shape, reducing the shading part of the battery cell, which means that the utilization efficiency of solar energy is increased.
[0041] (2) The evaporation temperature range of the organic solvent selected by the present invention is reasonable, and the uniform organic system formed by compounding multiple solvents with resins is highly compatible with the nickel plate, so that the thixotropic index of the slurry is within a reasonable range, which is conducive to the slurry being spread by a scraper during the printing process. Not only can screen printing be carried out smoothly, but the grid lines printed on the nickel plate are also very flat. In addition, after the slurry is cured, the resin will bond with the ITO film on the surface of the crystalline silicon cell, and has excellent flux resistance.
[0042] (3) The slurry of the present invention has good printability and fluidity and can be printed with narrow line width. It is not only suitable for conventional screen printing, but also highly suitable for nickel plate printing process.
[0043] 3. Good conductivity, high photoelectric conversion efficiency, and good low-temperature curing performance:
[0044] (1) The low-temperature conductive paste provided by the present invention is a mixture of multiple raw materials. The resin, curing agent, solvent and silver powder in the paste are reasonably matched. The paste can infiltrate the ITO velvet surface during the printing process, so that the cured gate line and ITO are more closely combined, the distance between the conductive phase and the battery cell is smaller, and the performance indicators such as contact resistance are better.
[0045] (2) The invention takes advantage of the excellent shrinkage of epoxy resin and uses it as a base resin in combination with sulfonyl dianiline and other curing agents. During the curing process, some addition-type curing agents can participate in the cross-linking structure of the resin, making the overall structure denser and improving the conductive properties of the slurry.
[0046] (3) The low-temperature conductive paste prepared by the present invention can produce excellent ohmic contact performance when used in HJT solar cells, thereby having excellent photoelectric conversion efficiency, and the loss of photoelectric conversion efficiency is less than 0.3%.
[0047] (4) The conductive paste of the present invention has the advantages of a wide curing window (150-200°C), does not require high-temperature sintering, is simple to use, has low body resistance, line resistance and contact resistance, high photoelectric conversion capability, and strong friction resistance of the printed gate lines. It is compatible with new printing technologies, is conducive to the promotion of HJT processes in the market, and has broad application prospects and market value. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is the grid line pattern after nickel plate printing in Example 1-3;
[0049] Figure 2 This is the grid line pattern after nickel plate printing in Example 1-2. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Embodiment 1:
[0052] This embodiment provides a method for preparing a HJT low-temperature conductive silver paste, comprising the following steps:
[0053] 1. 2.2% of liquid bisphenol A epoxy resin, 0.3% of acrylic resin, 1.4% of butyl carbitol, 0.8% of terpineol and 0.8% of diethylene glycol monobutyl ether were mixed and centrifuged at 1200 rpm for 3 minutes to prepare a uniform and transparent first organic carrier, which accounted for 5.5% of the total mass.
[0054] 2. 0.1% hexahydrophthalic acid, 0.3% m-phenylenediamine, and 0.4% sulfonyl dianiline were added to the first organic carrier, and centrifuged at 1400 rpm for 2 minutes to obtain a second organic carrier, which accounted for 6.3% of the total mass.
[0055] 3. Add 73.7% of micron-sized flaky silver powder and silver ball powder (the mass ratio of silver ball powder to silver flake powder is 3:7, the median particle size of silver ball powder is about 2um, and the median particle size of silver flake powder is about 4um) and 20% of pure silver ball powder with a median particle size of about 300nm to the above-mentioned organic carrier, add them three times, stir evenly after each addition, until all are added and stirred into a slurry, centrifuge the slurry at 600rpm for 1min and degas.
[0056] 4. After uniform dispersion, the prefabricated slurry is ground using a three-roll mill. The initial and final roll spacings of the three-roll mill are set to 90-30um, 60-20um, and 45-15um, and the roll speed is less than 200rpm. After grinding, the prefabricated slurry is dispersed at 500rpm for 2 minutes using a centrifuge, and then degassed to obtain a finished slurry with a metallic color.
[0057] Embodiment 2:
[0058] This embodiment provides a method for preparing a HJT low-temperature conductive silver paste, comprising the following steps:
[0059] 1. 1.9% of liquid bisphenol A epoxy resin, 0.3% of bisphenol F epoxy resin, 0.3% of glycidyl ester epoxy resin, 1% of oleic acid, 1.6% of pine alcohol, 0.1% of BYK111 and 0.2% of hydrogenated castor oil were mixed and centrifuged at 1200 rpm for 3 minutes to prepare a first organic carrier, which accounted for 5.4% of the total mass.
[0060] 2. 0.3% sulfonyl dianiline and 0.7% 2-ethyl-4-methylimidazole were added to the above organic carrier, and centrifuged at 1400 rpm for 2 min to obtain a second organic carrier, which accounted for 6.4% of the total mass.
[0061] 3. Add 73.6% of micron-sized flaky silver powder and silver ball powder (the mass ratio of silver ball powder to silver flake powder is 3:7, the median particle size of silver ball powder is about 2um, and the median particle size of silver flake powder is about 2um) to the above-mentioned organic carrier, as well as 12.5% of pure silver ball powder with a median particle size of about 300nm and 7.5% of pure silver ball powder with a median particle size of about 900nm. Add them three times, stir evenly after each addition, and stir into a slurry after all are added. Centrifuge the slurry at 500rpm for 2min and degas.
[0062] 4. Use a three-roll mill to grind the prefabricated slurry. The initial and final roll spacings of the three-roll mill are set to 90-30um, 60-20um, and 45-15um, and the roll speed is less than 200rpm. After grinding, use a centrifuge at 600rpm to disperse for 1min, and then degas to obtain a finished slurry with a metallic color.
[0063] Embodiment 3:
[0064] This embodiment provides a method for preparing a HJT low-temperature conductive silver paste, comprising the following steps:
[0065] 1. 2.3% of phenolic epoxy resin, 0.3% of diethylene glycol monobutyl ether, 2.4% of butyl carbitol, and 0.2% of silicone oil were centrifuged at 1200 rpm for 3 minutes to prepare a first organic carrier, which accounted for 5.2% of the total mass.
[0066] 2. 0.7% triethanolamine and 0.1% sulfonyl dianiline were added to the above organic carrier, and centrifuged at 1400 rpm for 2 min to obtain a second organic carrier, which accounted for 6% of the total mass.
[0067] 3. Add 74% of micron-sized flaky silver powder and silver ball powder (the mass ratio of silver ball powder to silver flake powder is 3:7, the median particle size of silver ball powder is about 1um, and the median particle size of silver flake powder is about 2um) and 20% of pure silver ball powder with a particle size of about 300nm to the above organic carrier, add them three times, stir evenly after each addition, until all are added and stirred into a slurry, disperse them evenly with a centrifuge and degas.
[0068] 4. Use a three-roll mill to grind the prefabricated slurry. The initial and final roll spacings of the three-roll mill are set to 90-30um, 60-20um, and 45-15um, and the roll speed is less than 200rpm. After grinding, use a centrifuge at 500rpm to disperse for 2 minutes, and then degas to obtain a finished slurry with a metallic color.
[0069] Comparative Example 1:
[0070] This comparative example provides a method for preparing a HJT conductive silver paste, comprising the following steps:
[0071] 1. 2.0% of liquid bisphenol A epoxy resin, 0.2% of acrylic resin, 0.3% of melamine urea-formaldehyde resin, 1.4% of butyl carbitol, 0.8% of pine alcohol, 0.7% of diethylene glycol monobutyl ether and 0.3% of polyamide wax were mixed and centrifuged at 1200 rpm for 3 minutes to prepare an organic carrier with high speed dispersion, which accounted for 5.7% of the total mass.
[0072] 2. Add 0.1% hexahydrophthalic acid, 0.3% m-phenylenediamine, and 0.4% sulfonyl dianiline to the above organic carrier, centrifuge at 1400 rpm for 2 minutes, and after high-speed centrifugation, the organic solvent accounts for 6.5% of the total mass.
[0073] 3. Add 77% of flaky silver powder with a median particle size of 2 microns and 16.5% of pure silver flake powder with a particle size of about 1 micron to the above organic carrier, disperse it evenly with a centrifuge after pre-stirring, use a three-roll mill to grind the prefabricated slurry, and then use a centrifuge to disperse and degas after grinding to obtain a finished slurry.
[0074] The process parameters not specified in the above preparation process are the same as those in Example 1, and the prepared slurry is a full-chip powder conductive slurry.
[0075] Comparative Example 2:
[0076] This comparative example provides a method for preparing a HJT conductive silver paste, comprising the following steps:
[0077] 1. 2% of bisphenol A epoxy resin, 0.3% of aliphatic compound, 0.3% of hydrogenated bisphenol A epoxy resin, 1.4% of butyl carbitol, 0.7% of diethylene glycol monobutyl ether, 0.5% of oleic acid, 1.6% of pine alcohol and 0.1% of BYK111 were mixed, centrifuged at 1200 rpm for 3 minutes, and dispersed at high speed to prepare an organic carrier accounting for 6.9% of the total mass.
[0078] 2. Add 0.2% hexahydrophthalic acid, 0.4% m-phenylenediamine and 0.5% sulfonyl dianiline to the organic carrier, centrifuge at 1400 rpm for 2 min, and the organic carrier obtained by high-speed centrifugation accounts for 8% of the total mass.
[0079] 3. Add 82% of pure silver spherical powder with a diameter of about 900nm and 10% of pure silver spherical powder with a particle size of about 300nm to the above organic carrier, disperse them evenly with a centrifuge after pre-stirring, use a three-roll mill to grind the prefabricated slurry, and then use a centrifuge to disperse and degas after grinding to obtain a finished slurry.
[0080] The process parameters not specified in the above preparation process are the same as those in Example 1, and the prepared slurry is a global powder conductive slurry.
[0081] Comparative Example 3:
[0082] This comparative example provides a method for preparing a HJT conductive silver paste, comprising the following steps:
[0083] 1. Mix 2.9% bisphenol A epoxy resin, 1% oleic acid, and 2% pine alcohol, centrifuge at 1200 rpm for 3 minutes, and disperse at high speed to prepare an organic carrier accounting for 5.9% of the total mass.
[0084] 2. 0.3% polyetheramine and 0.3% 2-ethyl-4-methylimidazole were added to the organic carrier, and centrifuged at 1400 rpm for 3 min. The organic solvent obtained after high-speed centrifugation accounted for 6.5% of the total mass.
[0085] 3. Add 73.5% of micron-grade pure silver flake powder and silver ball powder (the mass ratio of silver ball powder to silver flake powder is 3:7, the median particle size of silver ball powder is about 2um, and the median particle size of silver flake powder is about 4um) and 20% of pure silver ball powder with a particle size of about 300nm to the above-mentioned organic carrier, disperse them evenly with a centrifuge after pre-stirring, use a three-roll mill to grind the prefabricated slurry, and then use a centrifuge to disperse and degas after grinding to obtain a finished slurry.
[0086] The process parameters not specified in the above preparation process are the same as those in Example 1, and the prepared slurry is a spherical flake powder mixed silver paste.
[0087] Comparative Example 4:
[0088] The conductive silver paste prepared in Example 6 of Chinese patent application invention publication number CN117954145A “A high-reliability conductive silver paste for heterojunction solar cells and its preparation method” is used as comparative example 4.
[0089] Test Example 1:
[0090] The conductive pastes prepared in the above examples and comparative examples were subjected to the following performance tests, and the test methods are as follows:
[0091] (1) Volume resistance: Using silicon cell as substrate, manually print a rectangular pattern with a width of 5 mm and a length greater than 5 cm, and then cure it in an oven at 200°C for 7 min. The resistance and film thickness of the obtained sample were tested by a multimeter and a step profiler, and the volume resistance was obtained by substituting them into the formula.
[0092] (2) Photoelectric conversion efficiency: A screen printer was used with an opening of 18um on the front secondary grid plate, a printing speed of 300m / s, and an ink return speed of 1000mm / s. The conductive paste was printed on the silicon wafer and then cured at 200°C for 7min in a chain sintering furnace. The cured samples were tested for electrical properties by an IV tester (HSC1-1S, Shanghai Heshuang Solar Technology Co., Ltd.).
[0093] (3) Printing performance test: In addition to observing the ink return of the slurry during the printing process (the brush head drives the slurry to move repeatedly on the screen for printing. If the slurry can cover the entire screen every time, it is judged that the ink return is excellent), it is also necessary to use an EL tester to observe whether there is a broken grid on the screen after printing.
[0094] (4) Viscosity: The viscosity of the sample at 25°C was tested using a viscometer with a rotor of SC4-14, and the viscosity value was recorded when the rotor rotated at a speed of 10 rpm for 30 s.
[0095] (5) Adhesion test: Use 3M adhesive tape to adhere to the cured test pattern (cell for IV test), stick a piece of tape vertically, and use a high-grade drawing eraser to rub it flat. After leaving it for 1 minute, pull off the tape vertically and quickly (10cm / s) to observe whether the grid line of the cell falls off.
[0096] (6) Flux resistance test: Apply flux PV112B to the grid lines on the surface of the cell, then heat it on a heating table at 200°C for 15 seconds, and retest the cell short-circuit current (Isc), open-circuit voltage (Uoc), filling efficiency (FF) and photoelectric conversion efficiency (Eta) with an IV tester, and compare the results with those before application.
[0097] The test results of the above embodiments and comparative examples are shown in Table 1 and Table 2.
[0098] Table 1
[0099]
[0100] Table 2 Flux resistance test of examples and comparative examples
[0101] Key Metrics Isc Uoc FF Eta Example 1 -0.01% -0.08% -0.23% -0.30% Example 2 -0.41% 0.08% 0.13% -0.20% Example 3 -0.43% 0.07% -0.04% -0.15% Comparative Example 1 -0.41% 0.03% -0.08% -0.29% Comparative Example 2 -0.20% -0.11% -1.09% -1.40% Comparative Example 3 -0.58% -0.21% -1.41% -2.18% Comparative Example 4 0.24% -0.20% -2.43% -2.39%
[0102] It can be seen from Table 1 and Table 2 that Examples 1-3 of the present invention have excellent electrical properties and pass basic tests. They are used as metallization electrode slurries for low-temperature HJT heterojunction batteries and have excellent conductivity and good printing effects. In addition, they have excellent resistance to the flux applied during welding, and can control the efficiency loss of the slurry within 0.3%, which has broad application prospects.
[0103] It should be pointed out that there is a slight gap between the silver paste performance of the above-mentioned comparative example 4 and the silver paste performance of Example 6 of CN117954145A. This is due to the different manufacturers of the raw silver powder, and the surface coating processes of different silver powder manufacturers are also different, which further expands the performance difference of the prepared silver paste, but in general the difference is not significant.
[0104] Test Example 2: Nickel Plate Printing Test
[0105] Since the patterns of qualified products are slightly different after machine printing, the present invention only provides the patterns of qualified products and non-qualified products for intuitive comparison. Figure 1 As shown in the figure, it can be seen that the grid lines are regular, without misprinting or missing printing; the grid line pattern after nickel plate printing of comparative example 1-2 is as follows Figure 2 As shown in the figure, it can be seen that there are a lot of places where not enough slurry is printed. Figure 1 and Figure 2 It can be seen that when the type of silver powder is adjusted without considering the efficiency conversion, that is, the powder is tested with all flake powder or all spherical powder, even if the viscosity of the silver paste prepared with all flake powder and all spherical powder is very low, it is not helpful for nickel plate printing.
[0106] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A HJT low-temperature conductive silver paste for nickel plate printing, characterized in that: The conductive silver paste is composed of the following raw materials in percentage by mass: Micron-grade silver ball powder and silver flake powder 50-75%, submicron-grade spherical silver powder 18-44%, organic solvent 2-4%, curing agent 0.5%-1.5%, resin 2-4%, and auxiliary agent 0-1%.
2. The conductive silver paste according to claim 1, characterized in that: In the micron-sized silver ball powder and silver flake powder, the mass ratio of silver ball powder to silver flake powder is 2-3:6-7, the median particle size of the silver ball powder is 1-2um, and the median particle size of the silver flake powder is 2-4um; the median particle size of the submicron-sized spherical silver powder is 100-900nm.
3. The conductive silver paste according to claim 1, characterized in that: The organic solvent includes one or more of the following raw materials: pinene alcohol, oleic acid, butyl carbitol, butyl carbitol acetate, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dihydroacetic acid pine oil, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
4. The conductive silver paste according to claim 1, characterized in that: The curing agent includes one or more of the following raw materials: polyetheramine, polyamide, dicyandiamide, sulfonyl dianiline, meta-phenylenediamine, hexahydrophthalic anhydride, methylhexahydrophthalic acid dry, tetrahydrophthalic acid dry, 2-ethyl-4-methylimidazole, modified amine, modified imidazole, blocked polyamine, blocked isocyanate.
5. The conductive silver paste according to claim 4, characterized in that: The curing agent contains sulfonyl dianiline.
6. The conductive silver paste according to claim 1, characterized in that: The resin is selected from one or more of glycidyl ether epoxy resins, glycidyl ester epoxy resins, glycidyl amine epoxy resins, aliphatic epoxy compounds, alicyclic epoxy compounds, and modified epoxy resins.
7. The conductive silver paste according to claim 1, characterized in that: The auxiliary agent includes one or more of silane coupling agent, silicone oil, fluorosilicone, hydrogenated castor oil, polyvinyl pyrrolidone, lactic acid monoglyceride, sodium dodecyl sulfate, fumed silica, polyamide wax, BYK11, BYK10 and BYK354.
8. The method for preparing the conductive silver paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing a resin, an additive, and an organic solvent of a required mass, and obtaining a uniform and transparent organic system by centrifugal dispersion to obtain a first organic carrier; (2) adding a curing agent to the first organic carrier obtained in step (1), and mixing uniformly by mechanical stirring or by using a high-speed centrifuge to obtain a second organic carrier; (3) adding the micron-sized silver ball powder, silver flake powder, and submicron-sized spherical silver powder to the second organic carrier in three portions, stirring evenly after each addition, until all the powder is added and stirred into a slurry, and placing the slurry in a centrifuge for centrifugal dispersion and degassing; (4) The slurry obtained in step (3) is ground and dispersed by a three-roll mill, and then collected. The collected slurry is centrifuged again, and a finished product with a metallic color is obtained after degassing.
9. The preparation method according to claim 8, characterized in that: In steps (1) and (2), the centrifuge speed is 1200-1800 rpm, and the centrifugation time is 1-5 min. In steps (3) and (4), the centrifuge speed is 500-600 rpm, and the centrifugation time is 1-2 min.
10. The preparation method according to claim 8, characterized in that: In step (4), the initial roll spacing and the final roll spacing of the three-roll mill are set to 90-30um, 60-20um, and 45-15um, and the rolling speed is less than 200rpm.
